2013
DOI: 10.1097/fbp.0b013e32835efc5f
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian hormones and the heterogeneous receptor mechanisms mediating the discriminative stimulus effects of ethanol in female rats

Abstract: Past studies have suggested that progesterone-derived ovarian hormones contribute to the discriminative stimulus effects of ethanol, particularly via progesterone metabolites that have activity at γ-aminobutyric acid type A (GABAA) receptors. It is unknown whether loss of ovarian hormones in women, for example, after menopause, may be associated with altered receptor mediation of the effects of ethanol. The current study measured the substitution of allopregnanolone, pregnanolone, pentobarbital, midazolam, diz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Finally, the neurosteroid substitution patterns for ethanol suggest sex differences in sensitivity. For example, in contrast to earlier studies in male rats [33, 34], female rats showed only partial substitution of allopregna-nolone and pregnanolone for a 1 g/kg ethanol training dose [36]. This latter finding is consistent with earlier work demonstrating that females were less sensitive to the modulatory effects of allopregnanolone on ethanol drinking behavior when compared to males [37].…”
Section: 1 Rodentssupporting
confidence: 88%
See 2 more Smart Citations
“…Finally, the neurosteroid substitution patterns for ethanol suggest sex differences in sensitivity. For example, in contrast to earlier studies in male rats [33, 34], female rats showed only partial substitution of allopregna-nolone and pregnanolone for a 1 g/kg ethanol training dose [36]. This latter finding is consistent with earlier work demonstrating that females were less sensitive to the modulatory effects of allopregnanolone on ethanol drinking behavior when compared to males [37].…”
Section: 1 Rodentssupporting
confidence: 88%
“…From an initial characterization of several 5-HT receptor agonists in rats, the only compound to yield full substitution for ethanol in rats was TFMPP, a relatively nonselective 5-HT 1 agonist with slightly greater affinity for the 1A isoform [65]. This finding with TFMPP was replicated in both male [21] and female [36] rats. Subsequent evaluations of multiple compounds with various 5HT receptor agonist profiles in male rats revealed that CGS 12066B and CP 94,253 (both selective for 5-HT 1B ) or mCPP and RU 24969 (both selective for 5-HT 1B/2C ) fully generalized from ethanol (1 g/kg), whereas 8-OH DPAT (5-HT 1A ) and DOI (5-HT 2A ) did not 66–68].…”
Section: 1 Rodentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This limitation may be addressed by the utilization of a three-choice (e.g., alcohol, water, lysergic acid diethylamide-LSD) drug discrimination procedure (Grant, 1999), that could behaviorally capture a qualitative shift from the stimulus being less alcohol-like, and more like another stimulus (LSD, for example). Additionally, given the complexity of the alcohol discriminative stimulus (e.g., contribution of various transmitter systems: Helms, McCracken, Heichman, & Moschak, 2013; Hodge & Cox, 1998; Kostowski & Bieńkowski, 1999; Platt & Bano, 2011) it is unlikely that manipulation of one system (glutamate) would completely block expression of the interoceptive effects of alcohol, as we had predicted.…”
Section: Discussionmentioning
confidence: 75%